Optimal customer participation and the role of relationship length. Issue 5 (22nd March 2021) - Wang, Chung-Yu; Wu, Li-Wei; Wei, Chung-Lun
Abstract : Purpose: This study aims to examine how customers derive satisfaction and affective commitment from their participation in financial services, which is conditional on their relationship length. Design/methodology/approach: Student interviewers approached customers who were exiting banks at two skip intervals in Taiwan. The final survey sample consists of 227 respondents. Findings: Empirical results confirm that optimal customer participation (CP) influences affective commitment through increased customer satisfaction. The optimal level of CP with customer satisfaction and affective commitment is high if the relationship length is long. Originality/value: This article shows that the marginal benefits of CP on customer satisfaction and affective commitment become negative after an optimum level. Furthermore, relationship length moderates the aforementioned relationships.